Energy and macronutrients intake of children attending kindergartens in Kosovo (full day program-8 hours) - Rysha, Agim; Gjergji, Tahire M; Ploeger, Angelika (Progress in Nutrition, 2022)
Abstract: Aim: Understanding preschool children’s food consumption in kindergartens may be one possibility to find out whether preschool children’s energy is adequate. The aim of the study was to evaluate the energy and macronutrient intake by children in kindergartens in Kosovo. Methods: Preschool children (n = 469) aged 1<7 participated in three days’ dietary intake assessment through food measuring in kindergartens. The software Prodi was used to convert food items to constituent nutrients. The Anderson-Darling test was used to test if the dataset comes from a normal distribution. In contrast, Fisher’s and unpaired Student’s t-tests were used to see that data follow a normal probability distribution, the variances of the populations are equal, and the samples are independent. Analysis of Variance (ANOVA) was used to test the differences between means of energy and macronutrients among treatments (kindergartens). Results: The children obtained more than 50% of their daily energy requirements. The energy intake across the five kindergartens showed significant differences (between 292±31.7 kcal and 1126± 201 kcal). Apart from differences in the energy level, an imbalanced share of energy was observed from each macronutrient. Overall, children in our study met the recommended daily carbohydrate intake already during their 8 hours stay in kindergarten. The average protein intake by 1<4 old boys and girls exceeded the daily reference values for protein intake. The mean percentage of energy intake from fat was around 27 % of daily reference values. Conclusions: The energy intake across the five kindergartens showed significant differences and it was observed that there was an imbalanced share of energy from each macronutrient. There is a need for the development of uniform dietary legal standards of nutrition in kindergartens in Kosovo.